2011
DOI: 10.1111/j.1439-0272.2010.01114.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between seminal plasma arginase activity and spermatological parameters in rams

Abstract: This study was conducted to evaluate the correlation between seminal plasma arginase activity and spermatological parameters in rams. In this study, five fertility-proven Awassi rams were used as material. Six ejaculates were collected from each ram by an artificial vagina. Spermatological parameters (semen volume, mass activity, sperm motility and concentration and abnormal sperm rate) were immediately determined in each ejaculate. For enzyme assay, the semen samples were centrifuged and stored at -20 °C for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 26 publications
0
5
0
1
Order By: Relevance
“…However, there was an increase in seminal plasma arginase activity in vitamin E + selenium injected group, except for 72nd hr, but this increase was not statistically significant. Although some relationships between spermatological parameters and seminal plasma arginase activity have been reported (Gür & Kandemir, 2012;Türk, Gür, Kandemir, & Sönmez, 2011), no evidence was found effect of vitamin E and/or vitamin E + selenium combination on seminal plasma arginase activity.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…However, there was an increase in seminal plasma arginase activity in vitamin E + selenium injected group, except for 72nd hr, but this increase was not statistically significant. Although some relationships between spermatological parameters and seminal plasma arginase activity have been reported (Gür & Kandemir, 2012;Türk, Gür, Kandemir, & Sönmez, 2011), no evidence was found effect of vitamin E and/or vitamin E + selenium combination on seminal plasma arginase activity.…”
Section: Discussionmentioning
confidence: 90%
“…However, there was an increase in seminal plasma arginase activity in vitamin E + selenium injected group, except for 72nd hr, but this increase was not statistically significant. Although some relationships between spermatological parameters and seminal plasma arginase activity have been reported (Gür & Kandemir, ; Türk, Gür, Kandemir, & Sönmez, ), no evidence was found effect of vitamin E and/or vitamin E + selenium combination on seminal plasma arginase activity. However, in a study conducted by adding vitamin E and selenium to diet, a significant increase in cardiac and renal arginase activity and a decrease hepatic arginase activity was observed in vitamin E ingested group, but no difference was found in the vitamin E + selenium combination group compared to the control group (Erişir, Beytut, Ozan, & Aksakal, ).…”
Section: Discussionmentioning
confidence: 96%
“…It was found that plasma arginase activity was significantly lower than in the non-stress situation and during stress there was a negative correlation between the percentage of rapid progressive motility and arginase activity (Eskiocak et al, 2006). Similar relationships between the plasma arginase activity and the sperm concentration and sperm motility were detected in sheep and bulls (Gür et al, 2012;Türk et al, 2011). Although arginase activity has usually been detected in the reproductive tract, including spermatozoa, no data relating to the kinetic properties of enzyme in ejaculated spermatozoa has been reported.…”
Section: Introductionmentioning
confidence: 57%
“…Arginase activity was detected not only in spermatozoa, bu also in seminal plasma. A positive correlation has been shown between arginase activity and semen volume, semen mass activity, sperm motility and sperm concentration (Gür et al, 2012). It was found that plasma arginase activity was significantly lower than in the non-stress situation and during stress there was a negative correlation between the percentage of rapid progressive motility and arginase activity (Eskiocak et al, 2006).…”
Section: Introductionmentioning
confidence: 94%
“…Встановлено наявність позитивного кореляційного зв'язку між активністю аргінази і концентрацією сперматозоїдів, активністю аргінази й індексом рухливості сперматозоїдів. Аналогічні залежності між активністю аргінази сім'яної плазми та концентрацією і рухливістю сперматозоїдів виявлено у баранів і биків [15,16]. Слід зауважити, що отримані нами результати суперечать даним дослідників, які виявили, що аргіназна активність сперматозоїдів неплідних чоловіків з олігозооспермією є суттєво вищою, ніж у здорових донорів [13].…”
Section: методикаunclassified